Flammability testing of materials used in construction, transport, and mining - Apte, Vivek (Woodhead Publishing series in civil and structural engineering, 2021)
Flammability Testing of Materials used in Construction, Transport, and Mining, Second Edition provides an authoritative guide to current best practice in ensuring fire-safe design. The book begins by discussing the fundamentals of flammability, measurement techniques, and the main types of fire tests for various applications. Building on this foundation, a group of chapters then reviews tests for key materials used in the building, transport, and mining sectors. There are chapters on wood products, external cladding, and sandwich panels as well as the flammability of walls and ceilings linings. Tests for upholstered furniture and mattresses, cables, and electrical appliances are also reviewed. A final group of chapters discusses fire tests for the transport sector, including those for railway passenger cars, aircraft, road and rail tunnels, ships, and submarines. There is also a chapter on tests for spontaneous ignition of solid materials. With its distinguished international team of contributors, Flammability Testing of Materials used in Construction, Transport, and Mining is an invaluable reference for fire safety, civil, chemical, mechanical, mining and transport engineers. In this revised edition, the latest information is provided on fire testing of products, systems, components, and materials used across these essential sectors, with all regulations and standards brought up to date.